Real Driving Particulate Emissions from a Gasoline PHEV - Patel, Sahil Sanjay; Asakit, Jidapa (My University, 2020)
The gasoline Plug-In Hybrid Electric Vehicle (PHEV) has rapidly taken over the majority of the market share in terms of vehicle production and sales due to its reduced emission of exhaust pollutants and increased overall e ciency. This has augmented the importance of studying these emission levels, their behaviour and impact under real-world conditions. This study focuses on local tailpipe emissions such as NOX, particle number and size from a Gasoline PHEV. The study describes a Real Driving Emissions measurement of a gasoline PHEV in a test cell and on-road using a Portable Emissions Measurement System (PEMS). The measurement instruments used for this study are an AVL PEMS unit and Cambustion's DMS500 Fast Particulate Analyser. Similar amounts of PN from test-cell testings for the PEMS and DMS were found. A particle diameter study showed how the average size of particles emitted varies in the urban, rural and motorway sections. It has to be noted that the test vehicle used for this study does not qualify with on-road legislation. It is also concluded that numerous tests have to be carried out to obtain consistency and repeatability in test results to strengthen claims about the emission behaviour. The measurement capability of instruments used also plays an imminent role in this analysis as noticed with the test-cell data comparison between the PEMS and DMS systems.
Keywords: Real Driving Emissions; Portable Emissions Measurement System; Gasoline Plug-in Hybrid Electric Vehicle; Particulate Emissions